2015
DOI: 10.1177/1056789515620910
|View full text |Cite
|
Sign up to set email alerts
|

A new approach to the investigation of load interaction effects and its application in residual fatigue life prediction

Abstract: Fatigue damage under variable amplitude loading is related to load histories, such as load sequences and load interactions. Many nonlinear damage models have been developed to present load sequences, but load interactions are often ignored. This paper provides a new approach to present load interaction effects for nonlinear damage accumulation. It is assumed that the ratio of two consecutive stress levels is used to describe the phenomenon on damage evolution. By introducing the approach to a nonlinear fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 37 publications
(45 reference statements)
0
39
0
Order By: Relevance
“…The residual life fraction n 2 / N f 2 at σ 2 can be calculated by f(),σ1n1Nf1=f(),σ21n2Nf2. Previous researches have shown that the influence of load interaction can be well described by the load ratio. According to this, Peng et al developed a new prediction model of n 2 / N f 2 at σ 2 through modeling the fatigue damage evolution behavior as f(),σ1n1Nf1=fσ21n2Nf2σ1σ2. Combining Equations and , the residual life fraction at σ 2 under two block loadings is given by n2Nf2=1Nf2[]ln1n1Nf1lnNf1σ2σ1. …”
Section: Existing Nonlinear Fatigue Damage Accumulation Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…The residual life fraction n 2 / N f 2 at σ 2 can be calculated by f(),σ1n1Nf1=f(),σ21n2Nf2. Previous researches have shown that the influence of load interaction can be well described by the load ratio. According to this, Peng et al developed a new prediction model of n 2 / N f 2 at σ 2 through modeling the fatigue damage evolution behavior as f(),σ1n1Nf1=fσ21n2Nf2σ1σ2. Combining Equations and , the residual life fraction at σ 2 under two block loadings is given by n2Nf2=1Nf2[]ln1n1Nf1lnNf1σ2σ1. …”
Section: Existing Nonlinear Fatigue Damage Accumulation Modelsmentioning
confidence: 99%
“…In addition, the number of damage nuclei produced by different loading stress levels will lead to the change of damage accumulation, and this effect will increase with the larger difference between the stress levels. In this regard, similar to the work, a load ratio is introduced to describe the load interaction effects under two‐block loadings: n2Nf2=()1n1Nf1italiclnNf1italiclnNf2σ1σ2. …”
Section: Proposed Nonlinear Fatigue Damage Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The residual fatigue life depended on not only the effect of the loading sequence but also the loading history, especially the number of preloaded cycles. The existing models 9,33,[35][36][37] may be insufficient to account for the significant improvement of fatigue resistance induced by the previous low-amplitude fatigue loading history. Basaran et al [38][39][40][41][42][43][44][45][46][47] proposed a thermodynamic framework to describe the damage process of solid material under the fatigue loading.…”
Section: Introductionmentioning
confidence: 99%